CALCIUM DIFFUSIVITY IN ALUMINO-SILICATE GARNETS: AN EXPERIMENTAL AND ATEM STUDY - Vielzeuf D.; Baronnet A.; Perchuk A.L.; Laporte D.; Baker M.B. (My University, 2007)
Concentration gradients in calcium are common in metamorphic or magmatic garnets and can be used to determine the timescales of geological processes. However, the kinetics of Ca diffusion in garnet is poorly constrained and experimental studies have to date yielded widely varying diffusion coefficients. In this paper, we describe a new method for generating diffusion profiles in garnet. We incorporated polished and compositionally homogeneous garnet seeds in a finely ground powder of clinopyroxene and garnet. During the experiments (1.3 GPa, 1,050-1,250°C, and fO2 ≤ the graphite-O2 buffer), the mineral powder partially melted, recrystallized, and formed a 10-50 μm wide overgrowth zone of compositionally distinct garnet around the seeds. Long duration experiments generated measurable relaxation profiles at these seed/overgrowth interfaces. We performed analytical transmission electron microscope traverses across the interfaces in each experiment. Thirteen usable compositional profiles were obtained with characteristic distances of diffusion ranging from 300 to 1,000 nm. From these profiles, Ca-(Fe, Mg) interdiffusion coefficients were retrieved using an analytical solution for the diffusion equation and the data were cast in an Arrhenius relation. Linear regression of the data yields an activation energy QCa-(Fe,Mg) equal to 188 ± 48 kJ mol-1 and a frequency factor D0 equal to 6.6 × 10-14 m2 s-1. Within the compositional range studied, the composition of garnet has no major effect on the Ca-(Fe, Mg) interdiffusion coefficient. The very slow diffusion rate of Ca is in agreement with natural observations indicating that Ca diffuses more slowly than Fe and Mg. The Ca diffusion coefficients derived from this study are not model-dependent and can be used to determine the durations of geological events from Ca relaxation profiles in natural garnets. © Springer-Verlag 2007.